The Role of the Indonesian Army in Maintaining the Sovereignty of the Republic of Indonesia in the Indonesian Border Area With Timor Leste - Yahya, Yudhi; Widjayanto, Joni; Hendra, Afrizal (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Indonesian Army (TNI AD) is responsible for maintaining security and defense in border areas, as well as preventing threats that could undermine the sovereignty of the Republic of Indonesia (NKRI). This research aims to analyze the role of the TNI AD in safeguarding the sovereignty of the Republic of Indonesia in the border areas with Timor Leste. The research employs a qualitative method with descriptive analysis. The findings of this study indicate that the role of the TNI AD in safeguarding the sovereignty of the Republic of Indonesia in the border areas with Timor Leste encompasses various aspects, including border security, military operations, defense diplomacy, infrastructure development, and community empowerment. The TNI AD plays a crucial role in safeguarding the sovereignty of the Republic of Indonesia in border areas through routine patrols, maintaining territorial integrity, and supporting infrastructure development. Additionally, the TNI AD also contributes to ensuring the security and welfare of the communities in these border areas through community empowerment programs, including skills training, education, and economic assistance.